Consciousness Raising dan Partisipasi Politik Suku Baduy di Era Digital (Tinjauan Awal) - Mohamad Ghozali Moenawar; Wahyu Budi Priatna; Hudi Santoso (Institut Pertanian Bogor, 2019)
Development communication can play a role in the development of isolated rural communities from the metropolis world. The Baduy people that lives at the foot of the Kendeng Mountains in Kanekes Village, Leuwidamar District, Lebak-Rangkasbitung Regency, Banten, still maintains its customs and culture in the digital era. On the other hand, through the concept of critical awareness from Paulo Freire, the Baduy people is very likely to change towards a more dynamic condition. This study uses a qualitative method with an analytical descriptive approach, through interview techniques and library research. The results of the study indicate that consciousness raising as a process of development communication and community empowerment can be used as a tool to measure political participation in the Baduy people. Their significant involvement in the 2014 General Elections and 2017 Regional Elections (Pilkada) is proof of the Baduy people's compliance with government regulations. Even though in certain situations customary structures have the power to prohibit their people from participating in elections or regional elections.